Outcomes after extended pancreatectomy in patients with borderline resectable and locally advanced pancreatic cancer - Hartwig, Werner; Gluth, Alexander; Hinz, Ulf; Koliogiannis, Dionysios; Strobel, Oliver; Hackert, Thilo; Werner, Jens; Büchler, Markus W. (The British journal of surgery, 2016)
Background In the recent International Study Group of Pancreatic Surgery (ISGPS) consensus on extended pancreatectomy, several issues on perioperative outcome and long-term survival remained unclear. Robust data on outcomes are sparse. The present study aimed to assess the outcome of extended pancreatectomy for borderline resectable and locally advanced pancreatic cancer. Methods A consecutive series of patients with primary pancreatic adenocarcinoma undergoing extended pancreatectomies, as defined by the new ISGPS consensus, were compared with patients who had a standard pancreatectomy. Univariable and multivariable analysis was performed to identify risk factors for perioperative mortality and characteristics associated with survival. Long-term outcome was assessed by means of Kaplan-Meier analysis. Results The 611 patients who had an extended pancreatectomy had significantly greater surgical morbidity than the 1217 patients who underwent a standard resection (42·7 versus 34·2 per cent respectively), and higher 30-day mortality (4·3 versus 1·8 per cent) and in-hospital mortality (7·5 versus 3·6 per cent) rates. Operating time of 300 min or more, extended total pancreatectomy, and ASA fitness grade of III or IV were associated with increased in-hospital mortality in multivariable analysis, whereas resections involving the colon, portal vein or arteries were not. Median survival and 5-year overall survival rate were reduced in patients having extended pancreatectomy compared with those undergoing a standard resection (16·1 versus 23·6 months, and 11·3 versus 20·6 per cent, respectively). Older age, G3/4 tumours, two or more positive lymph nodes, macroscopic positive resection margins, duration of surgery of 420 min or above, and blood loss of 1000 ml or more were independently associated with decreased overall survival. Conclusion Extended resections are associated with increased perioperative morbidity and mortality, particularly when extended total pancreatectomy is performed. Favourable long-term outcome is achieved in some patients.